Quantitative Analysis of Videofluoroscopy Following Total Laryngectomy Using the ASPEKT Method - Smaoui, Sana; Lee, Sean M.; Ganesan, Sandhya; Ankeney, Emily; Ferraro, Tatiana; Dorward, Rebecca; Cardman, Erin‐Anne; Joshi, Arjun (Head & neck, 2025)
ABSTRACT Introduction Swallowing dysfunction is a common postoperative challenge for patients following total laryngectomy. Videofluoroscopic swallow study (VFSS) can be used to assess the mechanism of swallowing dysfunction in patients; however, many standardized protocols do not account for the anatomical changes in patients who have undergone total laryngectomy. In this study, we aim to utilize the ASPEKT (Analysis of Swallowing Physiology: Events, Kinematics & Timing) Method to quantify swallowing mechanics in a cohort of post‐laryngectomy patients. Methods A retrospective study of swallowing post total laryngectomy was performed. All participants received a VFSS as part of standard care up to 10 months following their surgery between 2011–2021. Blinded raters trained in the ASPEKT method scored the VFSS for: number of swallows, UES opening duration, pharyngeal area at maximum pharyngeal constriction (PhAMPC), and total pharyngeal residue. A mixed‐effects beta regression model was fitted to the data, with total pharyngeal residue as the dependent variable and number of swallows, UES duration, and pharyngeal area at maximum constriction as independent variables. Results The average number of swallows per bolus was greater than 2. For patients who required more than 1 swallow to clear the bolus, the average UES opening duration increased with each swallow, from 567 ms during the first swallow to 633 ms during the third swallow. Additionally, the average PhAMPC for patients who required more than one swallow was 40.4% C2–C42 compared with 22.2% C2–C42 in patients who cleared the bolus with one swallow. Results from the mixed‐effects beta regression model showed that PhAMPC (OR = 22.58; p < 0.001; [95% CI 7.39, 64.28]) was a significant predictor of residue. UES opening duration and number of swallows were not significantly predictive of total pharyngeal residue. Conclusions This study represents the application of the ASPEKT Method to more precisely analyze VFSS in patients following total laryngectomy. Changes in swallowing function and efficiency post‐laryngectomy may largely be attributed to ineffective maximal pharyngeal constriction. Future work further characterizing this change in swallowing dynamics is crucial in developing treatment options to address swallowing dysfunction following total laryngectomy.